Unlocking the Power of Intellectual Capital: Will it Increase the Entity Value? - Nurrahmawati, An; Chayati, Nur; Aini, Annisa Qurrota; Widarjo, Wahyu (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
This research examines the relationships between Intellectual Capital, Human Capital, Structural Capital, and Relationship Capital toward Firm Value in Indonesia's property and real estate companies. The aim is to analyse the power of intellectual capital in leveraging business performance. The target population for the study constituted all property and real estate sector companies in Indonesia total 215 observations within 2018-2022. The data was processed using an ordinary least square approach to gain the t-value of this relationship. This research measures the intellectual capital variable not from a financial or value-added perspective but from a descriptive side using for-way coding indicator. We found that relational capital has a significant positive relationship toward firm value. The study emphasized the need to change the proxy for firm value or to add some bridge between intellectual capital and financial performance to create a clear understanding.